ANALISIS PENGARUH AKSESIBILITAS, KONEKTIVITAS WILAYAH, DAN TATA GUNA LAHAN TERHADAP KEPUASAN PENGGUNA TRANSPORTASI LRT HARJAMUKTI KOTA DEPOK - Hanan Hadiwijaya, Raihan Putra; Adi Wijayanto, Pradika (Universitas Nahdlatul Ulama Blitar, 2025)
This study analyzes the influence of accessibility, regional connectivity, and land use on the satisfaction of Harjamukti LRT users in Depok City. A quantitative approach was applied using multiple linear regression analysis with SPSS version 26. Data were collected through questionnaires distributed to 100 active LRT users. The findings reveal that accessibility, connectivity, and land use have a positive and significant effect on user satisfaction both partially and simultaneously. Adequate accessibility improves station reachability and reduces travel burdens. Good intermodal connectivity facilitates seamless transfers and minimizes waiting time. Supportive land use around the station, such as commercial centers and residential areas, enhances comfort and user activities. Overall, the integration of these three factors improves travel experience, increases mobility efficiency, and provides policy recommendations for sustainable public transport development. These findings are essential for urban planners, transportation operators, and policymakers to design interventions that significantly promote massive public adoption of the LRT system.